Low levels of HIV-1 envelope-mediated fusion are associated with long-term survival of an infected CCR5−/− patient. (23rd October 2018) - Gorry, Paul R.; Ahmad, Fahim; Mohl, Jon; Alkhatib, Ghalib
Abstract : Objectives: This study investigated whether Env-mediated fusion levels of R5X4 viruses are associated with long-term survival of an infected CCR5−/− patient. Design: Four R5X4 Envs were cloned from each of two infected homosexual individuals (DR and C2) homozygous for the CCR5Δ32 allele. DR is a long-term survivor chronically infected with HIV-1 and his Envs were cloned 12 years after testing HIV-infected, whereas C2 Envs were isolated 1 year after primary infection. Methods: The current study sequenced the gp41 subunits and created hybrid Envs that contained exchanged gp41 subunits or V3 loops. The Env-mediated fusion activity of Envs was examined in cell fusion and virus infection assays. Results: Sequence analysis indicated novel polymorphisms in the gp41 subunits of C2 and DR, and revealed sequence homology between DR and certain long-term nonprogressors. The DR Envs consistently showed lower Env-mediated fusion, smaller size, and delayed onset of syncytia formation. Envs containing swapped gp41 regions resulted in the transfer of most of the fusion phenotype and in the shift of the inhibition concentration 50 (IC50) of the inhibitory T20 peptide. In contrast, Envs with swapped V3 domains resulted in the partial transfer of the fusion phenotype and no significant change in the IC50 of T20. Conclusions: Env sequence polymorphisms identified two distinct fusion phenotypes isolated from infected CCR5−/− patients. Swapping experiments confirmed DR's low fusion phenotype. Env-mediated fusion is a critical factor among others contributing to long-term survival. Abstract : Supplemental Digital Content is available in the text